2017
DOI: 10.3892/mmr.2017.6429
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 induces the phenotype transformation of human vascular smooth muscle cells via the canonical Wnt signaling

Abstract: Galectin‑3, a galactoside‑binding protein, is highly expressed in carotid plaques and plays an important role in the atherosclerotic lesions. The phenotype transformation of vascular smooth muscle cells is the basic pathological change of atherosclerosis. This study investigated the effects of exogenous galectin‑3 on the function and phenotype transformation of human umbilical vascular smooth muscle cells (HUSMC). In this study, we treated vascular smooth muscle cells with recombinant galectin‑3 and tested its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Numerous studies have demonstrated that thrombin promotes cellular migration (25,26). Gal-3 is an anti-adhesive factor that promotes SMC migration and may accelerate atherogenesis (16,27). In our research, we found that thrombin increased gal-3 expression.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Numerous studies have demonstrated that thrombin promotes cellular migration (25,26). Gal-3 is an anti-adhesive factor that promotes SMC migration and may accelerate atherogenesis (16,27). In our research, we found that thrombin increased gal-3 expression.…”
Section: Discussionsupporting
confidence: 60%
“…Acute MI increases gal-3 level, which is positively correlated with left ventricular ejection fraction (LVEF) (14,15). Besides, in our previous research, gal-3 was found to promote VSMC migration via the Wnt/β-catenin signaling pathway (16).…”
Section: Introductionmentioning
confidence: 83%
“…Tian et al reported that Gal-3 expression increased in the phenotypic transformed VSMC treated with ox-LDL. Small interfering RNA silencing or knockdown of Gal-3 inhibited the phenotypic transformation and migration of VSMC[48], and another study of Tian et al particularly indicated that exogenous Gal-3 promoted human VSMC proliferation and migration through the activation of canonical Wnt/β-catenin signaling pathway[49].…”
mentioning
confidence: 97%
“…Oxidized low-density lipoprotein (oxLDL) increases the expression of gal3 in VSMCs [4]. Gal3 also induces fibroblast and VSMCs to proliferate and produce fibrosis-related proteins in the extracellular matrix [8,9]. Strategies to inhibit gal3 induce decreased atherosclerosis and may reduce plaque progression [7,10].…”
Section: Introductionmentioning
confidence: 99%